2011
DOI: 10.1111/j.1365-2915.2011.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial stratification of host‐seeking Diptera in boreal forests of northern Europe

Abstract: The stratification of haematophagous Diptera was assessed in two boreal forests in northern Sweden by placing traps baited with carbon dioxide at 1.5 m, 5.0 m and 10.0 m above the ground. More than 40 000 specimens were captured, including 617 biting midges (Ceratopogonidae), 4029 mosquitoes (Culicidae) and 36 092 black flies (Simuliidae). Catches at the various trap heights reflected the general vertical distribution of the preferred hosts, with mammalophilic flies predominating (68.6%) in catches at 1.5 m an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
4
13
0
Order By: Relevance
“…It is known that the vertical distribution of haematophagous Diptera can be influenced by their hosts [67, 68]; that no blackfly species is exclusively anthropophilic [37], and that degrees of anthropophily vary among human biting members of the S . damnosum complex [69].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the vertical distribution of haematophagous Diptera can be influenced by their hosts [67, 68]; that no blackfly species is exclusively anthropophilic [37], and that degrees of anthropophily vary among human biting members of the S . damnosum complex [69].…”
Section: Discussionmentioning
confidence: 99%
“…Blood-sucking flies may choose a particular level above ground and feed on a range of hosts encountered at that level [34,35]. Swanson et al [36] observed that the largest catch of C. pictipennis was at 10 m above the ground in a spruce forest and was thus associated with avian hosts. The low catch of blood-fed C. pictipennis (n = 9) in this present study by traps at ground level and the identified blood meals from magpie (n = 2) suggests a similar association.…”
Section: Discussionmentioning
confidence: 99%
“…The low catch of blood-fed C. pictipennis (n = 9) in this present study by traps at ground level and the identified blood meals from magpie (n = 2) suggests a similar association. Swanson et al [36] also observed a relatively high number of C. salinarius Kieffer specimens (n = 15) near ground level in a pine forest, and therefore associated this species with mammal hosts. We caught a single blood-fed C. salinarius near the ground at the hobby farm near Knabstrup that had fed from a tree sparrow ( Passer montanus L.).…”
Section: Discussionmentioning
confidence: 99%
“…In both years, trapping began before the emergence of black flies. Because trap height can influence collecting efficacy (Russell and Hunter 2005, Swanson et al 2012), we placed the traps about 150 cm above the water, the approximate height of a whooping crane's head while on a nest.…”
Section: Methodsmentioning
confidence: 99%